Differential expression of novH and CTGF in human glioma cell lines. Issue 2 (April 1996) - Xin, L W; Martinerie, C; Zumkeller, W; Westphal, M; Perbal, B
Abstract : Aims —(1) To investigate the expression in human derived glioblastoma cell lines of two structurally related genes, nov H (nephroblastoma overexpressed gene) and CTGF (connective tissue growth factor), which encode putative insulin-like growth factor binding proteins of a novel type. (2) To investigate whether the same transcription factors regulate CTGF and nov H expression. Methods —Expression of nov H and CTGF was analysed in 24 glioblastoma derived cell lines by northern blotting. The CTGF promoter region was characterised by nucleotide sequencing, RNase protection experiments, by transient transfections, and CAT assays. Results —CTGF and nov H mRNA levels differed in the glioma cell lines studied. Nov H and CTGF genes were not co-expressed in all cell lines. The CTGF promoter region was highly conserved compared with the corresponding region in the mouse (FISP12) and exhibited in vitro transcriptional activity. Conclusions —Although the coding regions of nov H and CTGF are highly homologous, their promoter regions are substantially different, suggesting that these two genes may be regulated by different mechanisms. Considering that nov H and CTGF are likely to be, respectively, negative and positive regulators of growth and that some glioma cell lines expressing nov H are not tumorigenic, expression of these two genes might represent a key element in determining the stage of differentiation or the malignant potential, or both, of some tumour cell lines.